Developmental transcriptomics of the Firebrat: Exploring developmental expression patterns and morphology during the embryogenesis of Thermobia domestica - Wouter P. D. Makkinje; Esther te Lindert-Blommert; Robin van Velzen; Eric Schranz (PLoS ONE, 2025)
Understanding the development of early-diverging lineages is crucial for inferring evolutionary context in evolutionary developmental biology. Thermobia domestica (the firebrat), a member of Zygentoma, holds particular significance to insect phylogenetics due to its position as a sister group to all winged insects (Pterygota). We explore its development by reporting on the embryonic morphology using DAPI staining at 14 selected timepoints throughout development, which lasts 10 days. At each timepoint, RNA sequencing was conducted to perform a large-scale transcriptomic analysis. Differential gene expression analysis and gene ontology (GO) enrichment studies revealed global expression patterns and linked biological processes to specific developmental stages. Key findings include the identification of major transcriptional turning points during three developmental stages: The maternal to zygotic transition between 16 and 24 hours after egg-laying (hAEL), katatrepsis between 72 and 96 hAEL, and hatching between 216 and 240 hAEL. Additionally, the GO study mapped the timing of biological processes, such as cleavage, blastoderm formation, dorsal closure, and organogenesis, particularly tracheal and muscular development. These insights establish a robust temporal framework for T. domestica embryogenesis and provide a foundation for inferring ancestral and derived developmental traits in insects. The dataset serves as a valuable library for genetic studies and reference for comparative evo-devo studies with other insect species.